1996
DOI: 10.1161/01.cir.93.7.1417
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Peripheral Pulmonary Artery Stenoses in the Adult

Abstract: We describe a severe syndrome of isolated PPS in the adult that mimics chronic pulmonary thromboembolic disease. Pulmonary hemodynamics and angiography are required for definitive diagnosis. BPA may offer these patients successful short-term reduction in RV hypertension and alleviation of symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
3
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 41 publications
3
96
3
1
Order By: Relevance
“…5,6 Over the past decade, improvements have included use of (1) soft-tipped, highly maneuverable guidewires; (2) a modified pigtail catheter that permits angiography while maintaining wire position 7 ; (3) low profile balloons; (4) improved nonionic contrast agents; and (5) full heparin anticoagulation before, during, and after the procedure. The BPA of experimentally induced pulmonary arterial narrowings in animals, in conjunction with registry collection of clinical experience in patients with congenital peripheral pulmonary stenoses, has confirmed that optimal dilation can be obtained with balloons sized 200% to 400% the diameter of the stenotic region but Յ150% the diameter of the surrounding vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Over the past decade, improvements have included use of (1) soft-tipped, highly maneuverable guidewires; (2) a modified pigtail catheter that permits angiography while maintaining wire position 7 ; (3) low profile balloons; (4) improved nonionic contrast agents; and (5) full heparin anticoagulation before, during, and after the procedure. The BPA of experimentally induced pulmonary arterial narrowings in animals, in conjunction with registry collection of clinical experience in patients with congenital peripheral pulmonary stenoses, has confirmed that optimal dilation can be obtained with balloons sized 200% to 400% the diameter of the stenotic region but Յ150% the diameter of the surrounding vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The BPA of experimentally induced pulmonary arterial narrowings in animals, in conjunction with registry collection of clinical experience in patients with congenital peripheral pulmonary stenoses, has confirmed that optimal dilation can be obtained with balloons sized 200% to 400% the diameter of the stenotic region but Յ150% the diameter of the surrounding vessel. 6 At present, there are insufficient pathological studies of the vascular wall and its response to injury in distal vessels affected by CTEPH. Therefore, to minimize the potential for vessel rupture, we reasoned that the maximal balloon size should be less than or equal to the surrounding vessel size.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, Takayasu arteritis and Behçet disease have been associated with pulmonary artery stenoses that required immunosuppressive therapy and pulmonary artery balloon angioplasty with or without stenting. [11][12][13][14][15] Isolated cases of PPAS in adulthood have been seldom reported, 7,8,16 a fact that can reflect a low prevalence of the disease in addition to underrecognition and misdiagnosis. 16 These last two factors are of great relevance, since patients may not receive appropriate treatment (i.e., balloon or stent angioplasty) or the therapy might be inappropriate for PPAS (i.e., PH-specific therapies or pulmonary thromboendarterectomy).…”
mentioning
confidence: 99%
“…10,11,14 However, the problems of these surgical procedures including graft reocclusion, anastmotic site aneurysm, and morbidity have precluded the widespread use of reconstructive surgery. Kreutzer et al 15 performed balloon dilation of multiple vessels in 11 patients. The authors suggested that balloon dilation offered successful short-term reduction in right ventricular hypertension and alleviation of symptomatology.…”
Section: Discussionmentioning
confidence: 99%